Potensi Hunian Gua dan Ceruk di Kabupaten Aceh Besar - Taufiqurrahman Setiawan (Balai Arkeologi Yogyakarta, 2020)
The evidence of prehistoric life in Aceh has been proven by the results of archeological research conducted by the North Sumatra Archaeological Institute. Until now, the research only focuses on the eastern coast and the central mountains of Aceh. The western coast of Aceh, which also has the potential to provide information, has never been studied. The western coast of Aceh is an area that has a wide karst landscape with many caves that might be used as a settlement in the past. One method used to predict such caves included a topographic map, a geological map, and a digital elevation model (DEM). The inventory results of caves on the western coast of Aceh were also used as preliminary data to obtain the distribution of caves and rock shelters. In this study, the area surveyed was Aceh Besar Regency. Three parameters of inhabited caves, i.e. morphology and genesis, environment, and archaeological content, were used to describe the potential of each cave. Of eleven caves and rock shelters, three caves are qualified as the past settlement and potential for further research, four caves are qualified as the past settlement but not potential for further research, and four caves are neither qualified as a settlement nor potential for further research.